(untitled) (Veterinária Notícias, 2018)
A dog was consulted with functional disability of the right thoracic limb. Radiographic image showed lateral luxation of the scapulohumeral joint. The animal was submitted to surgical treatment using tension suture with screws and Nylon wire, with satisfactory result and functional use of the limb 30 days postoperatively.